2022
DOI: 10.1038/s41598-022-14480-8
|View full text |Cite
|
Sign up to set email alerts
|

Global warming is shifting the relationships between fire weather and realized fire-induced CO2 emissions in Europe

Abstract: Fire activity has significantly changed in Europe over the last decades (1980–2020s), with the emergence of summers attaining unprecedented fire prone weather conditions. Here we report a significant shift in the non-stationary relationship linking fire weather conditions and fire intensity measured in terms of CO2 emissions released during biomass burning across a latitudinal gradient of European IPCC regions. The reported trends indicate that global warming is possibly inducing an incipient change on regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 61 publications
(82 reference statements)
1
26
0
Order By: Relevance
“…As continued increases in summer aridity are projected for Europe (Balting et al, 2022), we conclude that the stable development of area burned observed for Europe over the past decades will likely change to increased fire activity in the near future. Forest management and policy in Europe thus need to prepare for a future with larger and more severe fires, and develop strategies to mitigate fire-related impacts on forest carbon (Carnicer et al, 2022), resilience (Turner et al, 2022) and biodiversity (Palm et al, 2022).…”
Section: Discussion and Con Clus I On Smentioning
confidence: 99%
“…As continued increases in summer aridity are projected for Europe (Balting et al, 2022), we conclude that the stable development of area burned observed for Europe over the past decades will likely change to increased fire activity in the near future. Forest management and policy in Europe thus need to prepare for a future with larger and more severe fires, and develop strategies to mitigate fire-related impacts on forest carbon (Carnicer et al, 2022), resilience (Turner et al, 2022) and biodiversity (Palm et al, 2022).…”
Section: Discussion and Con Clus I On Smentioning
confidence: 99%
“…In the maritime pine forest, the average seasonal FWI is expected to almost double, from an average of 11. the values obtained for this year, which was marked by many large fires in the North of the country. Impacts on fire-induced CO2 emissions might in addition shift toward more emitting fire events (Carnicer et al, 2022).…”
Section: Biomass-based Vulnerability Assessment Redefines the 2022 Di...mentioning
confidence: 99%
“…The development of efficient separation technology is urgently required to capture CO 2 from ue gas and achieve the goal of carbon neutrality. [1][2][3] In addition, CH 4 /N 2 separation is also challenging but needed in the upgrading of unconventional natural gas. 4 Membrane-based separation technology offers signicant merits over other gas separation technologies, including energy efficiency, low cost, and simple process design, and thus shows broad prospects in industrial gas separation.…”
Section: Introductionmentioning
confidence: 99%